2020
DOI: 10.3390/d12090346
|View full text |Cite
|
Sign up to set email alerts
|

Climate Change and Alpine Screes: No Future for Glacial Relict Papaver occidentale (Papaveraceae) in Western Prealps

Abstract: Glacial relicts, especially those with very narrow habitat requirements, are particularly affected by global warming. We considered Papaver occidentale, a glacial relict endemic to the Western Prealps, belonging to the alpine poppy complex (P. alpinum aggr.), as a model taxon to study the actual status and potential future distribution of species restricted to particular microrefugia. For this study, all known localities were visited, each population was georeferenced and the number of individuals was estimate… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 69 publications
0
7
0
Order By: Relevance
“…The effects of climate change on the distribution of alpine species does not follow a fixed pattern, with impacts varying with the species’ life history and resource requirements. While several studies predict a dramatic decline in suitable habitat of alpine floral species with climate change ( Frishkoff et al, 2016 ; Fragnière et al, 2020 ), there are some species that also benefit from it and may cover larger area in the future ( Wang et al, 2019 ). For instance, the distribution of alpine herb specie Pedicularis kansuensis is expected to expand with climate change, under RCP scenarios RCP 2.6 and RCP 8.5, with a northward shift in distribution ( Wang et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effects of climate change on the distribution of alpine species does not follow a fixed pattern, with impacts varying with the species’ life history and resource requirements. While several studies predict a dramatic decline in suitable habitat of alpine floral species with climate change ( Frishkoff et al, 2016 ; Fragnière et al, 2020 ), there are some species that also benefit from it and may cover larger area in the future ( Wang et al, 2019 ). For instance, the distribution of alpine herb specie Pedicularis kansuensis is expected to expand with climate change, under RCP scenarios RCP 2.6 and RCP 8.5, with a northward shift in distribution ( Wang et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the distribution of alpine herb specie Pedicularis kansuensis is expected to expand with climate change, under RCP scenarios RCP 2.6 and RCP 8.5, with a northward shift in distribution ( Wang et al, 2019 ). Meanwhile suitable area for the alpine plant Papaver occidentaleis would decrease considerably in the coming decades ( Fragnière et al, 2020 ). Climate warming is expected to promote seedling emergence phenology in other alpine herbs such as Primula alpicola , Pedicularis fletcheri , Meconopsis integrifolia and M. racemose ( Wang et al, 2018 ), while species such as Canacomyrica monticola and Fritillaria cirrhosa face threats of rapid habitat loss and extinction ( Davies et al, 2009 ; Kumar and Stohlgren, 2009 ; Barnosky et al, 2011 ; Wang J. J. et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…As a result of the low vegetation cover, plants occurring on the screes are exposed to wind and other harsh weather conditions that are typical for high altitudes (Fisher 1952). Such extreme conditions impact not only plant life (Fragnière et al 2020) but also pollinator abundance and consequently also outcrossing rates (Mathews and Collins 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In general, the species would tend to distribute to high latitudes or elevations in the future to achieve a suitable habitat under continuous climate warming. Previous studies have demonstrated that numerous species change their geographic distribution range towards high latitudes and altitudes [1,16,17]. However, an increasing number of reports have found other types of range changes, such as east-west directions across longitudes or towards low elevations and tropical latitudes [42].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, it requires only species presence data, can deal effectively with limited occurrence data and small sample sizes, and can use continuous and categorical environmental data as input variables. Numerous studies have predicted changes in animal and plant distributions in response to contemporary climate changes using the Maxent model [7,[16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%